Budaya Westernisasi Terhadap Masyarakat - Dzakiy Muhammad Alfadhil; Agung Anugrah; Muhammad Hafiz Alfidhin Hasbar (Journal Social Politica, 2021)
Culture is dynamic and can grow and develop along with changing times because culture is built and rebuilt by humans However, there are cultures that cannot changed. Koentjaraningrat divides culture into two forms of culture, namely culture and culture physical and non physical (Koentjaraningrat 1982). Culture that is physical in the form of a product and difficult to change, such as temples and inscriptions. While non-physical culture is present in the form of ideas and dynamic human activities, open to change and adaptation to the context of the times. The influence of Western culture or what is known as ''Westernization'' is clearly visible today.